Rekonstruksi Kerangka Hukum Penyadapan di Peradilan Pidana Indonesia Berasas Due Process of Law - Muhammad Ariq Aditya; Elly Sudarti; Elizabeth Siregar (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
The problem surrounding the fragmentation of wiretapping regulations in the Indonesian criminal justice system and the formulation of an ideal policy based on the principle of due process of law. The research method used is normative legal analysis using a juridical approach and a conceptual approach. The results of this study indicate that current wiretapping practices are often carried out without a strict court approval mechanism at the initial stage, making them vulnerable to abuse of authority. In addition, the lack of transparency, the absence of a single standard regarding the duration of wiretapping, and the absence of provisions regarding the deletion of wiretapping data create potential loopholes for human rights violations. The theories used include the Theory of Legal Certainty, the Theory of Criminal Law Policy, the Theory of Authority, the Theory of Human Rights, and the Theory of the Criminal Justice System. This study recommends the development of law for all towards the enactment of a special law on wiretapping as an umbrella regulation that harmonizes it.